Trichoderma hamatum derived from coffee plant ( Coffea canephora ) rhizosphere inhibit Candida albicans Growth - Yuyun Nisaul Khairillah; Nampiah Sukarno; Irmanida Batubara (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
The Trichoderma hamatum produces various secondary metabolites that can be used as Candida albicans. This research aimed to isolate T. hamatum from the coffee (Coffea canephora) rhizosphere and analyze the fungal compounds to control the pathogenic fungus C. albicans. T. hamatum was isolated using the dilution method, and the fungal identification was used, combining morphological and molecular characteristics of ITS rDNA. The potency of T. hamatum as C. albicans was determined by antagonist test using the double-layer method, while for culture filtrate, ethyl acetate and n-hexane filtrate extracts were carried out by the agar diffusion method. The compounds in the most active extract were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). T. hamatum inhibits C. albicans growth in antagonistic and filtrate with 15.53 mm and 14.40 mm of inhibition zone. It indicated that both culture and fungal filtrate had similar activities on C. albicans. The ethyl acetate extract (minimum inhibitory concentration, MIC of 0.50%) showed more potent against C. abicans than n-hexane extract (MIC of 15.00%). The potential active compound in the ethyl acetate extract would be 9-Octadecenoic acid (Z) methyl ester. The 9-Octadecenoic acid (Z) methyl ester could be used as an alternative candidate to control Candida.